Implementasi One Health dalam Strategi Diplomasi Kesehatan Global Indonesia di Era Pandemi Covid-19 - Dian Alma Clara Manihuruk (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
This study examines the implementation of the One Health approach in Indonesia's global health diplomacy during the COVID-19 pandemic. The One Health approach, integrating human, animal, and environmental health, is key in addressing complex global health challenges. Indonesia's participation in the COVAX Facility demonstrates the country's commitment to strengthening global health security and resilience. This study employs a qualitative descriptive method to explore how Indonesia utilized One Health as a diplomatic tool in managing the pandemic. The findings highlight that through health diplomacy, Indonesia not only enhanced regional and global health cooperation but also addressed various operational and strategic challenges during the pandemic. This analysis contributes to a deeper understanding of the importance of integrating health sectors in international diplomacy and provides insights into the implementation of One Health in public health emergency contexts
Reaploud Repository February 2026_Hasyim
Keywords: One Health; global health diplomacy; COVAX Facility; Indonesia; COVID-19 pandemic